1972
DOI: 10.1172/jci106854
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Bactericidal, Metabolic, and Lysosomal Functions of Chediak-Higashi Syndrome Leukocytes

Abstract: A B S T R A C T Phagocytic, antimicrobial, and metabolic functions were studied in leukocytes obtained from three patients with the Chediak-Higashi syndrome (CHS) and compared to normals, individuals, heterozygous for Chediak-Higashi syndrome, and two subjects with chronic granulomatous disease of childhood (CGD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
1
2

Year Published

1976
1976
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(120 citation statements)
references
References 35 publications
8
109
1
2
Order By: Relevance
“…Stimulation of isolated leukocytes clearly indicated a deficient mobilization of myeloperoxidase and lysozyme on Ionomycin stimulation, indicating an almost complete lack of giant granule mobilization, which may well explain the delayed bacterial killing observed in CHS [7,8]. We found a more pronounced reduction in mobilization of myeloperoxidase than previously published by others [10,11].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Stimulation of isolated leukocytes clearly indicated a deficient mobilization of myeloperoxidase and lysozyme on Ionomycin stimulation, indicating an almost complete lack of giant granule mobilization, which may well explain the delayed bacterial killing observed in CHS [7,8]. We found a more pronounced reduction in mobilization of myeloperoxidase than previously published by others [10,11].…”
Section: Discussionsupporting
confidence: 62%
“…The hallmark of the disease is the presence of giant granules in most nucleated cells, including neutrophils. The propensity for infections in CHS is believed in part to be due to neutropenia and to deficient chemotaxis and delayed bacterial killing of neutrophils [6][7][8]. The latter is most likely caused by reduced content of certain microbicidal/cytotoxic proteins in CHS neutrophils [9] and by diminished mobilization of the giant granules [7,10,11], which contain the majority of the microbicidal substances of neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…1, Tables 2 and 3). This is in contrast to the findings of others who have noted normal phagocytosis but delayed killing of some bacterial strains by granulocytes from CHS patients (Root, Rosenthal and Balestra, 1972) and from beige mice (Gallin et al, 1974). These granulocytes have been shown to have a specific protease deficiency (Vassalli et al, 1978).…”
Section: Discussioncontrasting
confidence: 99%
“…Abnormalities include poor mobilization of neutrophils from the marrow [31], defective chemotactic response of neutrophils and monocytes [32,33] and decreased bactericidal activity [34]. In vivo skin window studies also demonstrated defective neutrophil migration [32].…”
Section: Discussionmentioning
confidence: 99%